Phytofabrication of Silver Nanoparticles Using Three Flower Extracts and Their Antibacterial Activities Against Pathogen Ralstonia solanacearum Strain YY06 of Bacterial Wilt - Cheng, Hai-Jun; Wang, Hui; Zhang, Jing-Ze (Frontiers in Microbiology, 2020)
Bacterial wilt caused by the phytopathogen Ralstonia solanacearum (R. solanacearum) is a devastating plant disease worldwide. The use of bactericides and antibiotics for controlling bacterial wilt has shown low efficiency and posed environmental risks. This study was to phytofabricate AgNPs mediated by Canna lily flower (Canna indica L.), Cosmos flower (Cosmos bipinnata Cav.) and Lantana flower (Lantana camara L.). The biosynthesized AgNPs were confirmed and characterized by UV–Visible spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), transmission electron microscope (TEM) and scanning electron microscopy (SEM). UV-visible spectra showed absorption peak bands at 448, 440, and 428 nm of AgNPs synthesized by Canna indica L., Cosmos bipinnata Cav. and Lantana camara L. flowers respectively. FTIR spectra confirmed that biofunctional groups of flower extract were involved in the synthesis of AgNPs as capping and stabilizing agents. The spherical AgNPs synthesized by Canna indica L., Cosmos bipinnata Cav. and Lantana camara L. flowers had average diameters of 43.1, 36.1, and 24.5 nm respectively. The AgNPs (10.0 µg/ml) synthesized by Lantana camara L. flower had a maximum suppression zone of 18 mm against Ralstonia solanacearum strain YY06 compared with AgNPs synthesized by Canna indica L. and Cosmos bipinnata Cav. flowers. bacterial growth, biofilm formation, swimming motility, efflux of Nucleic acid, cell death, cell membrane damage, Reactive oxygen species (ROS) generation of R. solanacearum were also negatively affected by silver nanoparticles with high concentration and small size. In summary, The biosynthesized AgNPs can be used as an efficient and environmentally friendly antibacterial agent to reasonably inhibit Ralstonia solanacearum.